Dissecting the Variations of Ripening Progression and Flavonoid Metabolism in Grape Berries Grown under Double Cropping System - Chen, Wei-Kai; Bai, Xian-Jin; Cao, Mu-Ming; Cheng, Guo; Cao, Xiong-Jun; Guo, Rong-Rong; Wang, Yu; He, Lei; Yang, Xiao-Hui; He, Fei; Duan, Chang-Qing; Wang, Jun (Frontiers in Plant Science, 2017)
A double cropping system has been commercially adopted in southern China, where there is abundant sunshine and heat resources. In this viticulture system, the first growing season normally starts as a summer cropping cycle; then, the vine is pruned and forced, resulting in a second crop in winter. Due to climate differences between the summer and winter growing seasons, grape ripening progression and flavonoid metabolism varies greatly. Here, the metabolites and transcriptome of flavonoid pathways were analyzed in grapes grown under two growing seasons at different stages. Notably, the winter cropping cycle strongly increased flavonoid levels by several times in comparison to summer grapes, while the summer season took a major toll on anthocyanin and flavonol accumulation, since the winter cropping greatly triggered the expression of upstream genes in the flavonoid pathway in a coordinated expression pattern. Moreover, the ratio of VviF3’5’Hs (flavonoid 3’5’-hydroxylase) to VviF3’Hs (flavonoid 3’-hydroxylase) transcript levels correlated remarkably well with the ratio of 3’5’-substituted to 3’-substituted flavonoids, which was presumed to control the flux of intermediates into different flavonoid branches. On the other hand, the phenological phase also varied greatly in the two crops. Compared to summer cropping, winter growing season accelerated the duration from budburst to veraison, therefore advancing the onset of ripening, but also prolonging the duration of ripening progression due to the purposes to harvest high quality grapes. The differential expression pattern of hormone-related genes between the two cropping cycles might explain this phenomenon.